2023
DOI: 10.1039/d2dt03311a
|View full text |Cite
|
Sign up to set email alerts
|

2D bimetallic organic framework nanosheets for high-performance wearable power source and real-time monitoring of glucose

Abstract: Ultra-thin 2D bimetallic organic framework nanosheets were fabricated as electrode materials for flexible wearable power sources and non-invasive blood glucose monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The 2D NiCo-MOF nanosheet array electrode has excellent glucose detection performance with a linear range of 1 μM~8 mM, fast response time of less than 1 s, sensitivity of 0.6844 mA·mM −1 cm −2 and LOD as low as 0.29 μM ( Figure 4 C). Zha and co-workers used a simple solvothermal method to synthesize 3D nanoflower-like bimetallic NiCo-MOF consisting of 2D nanosheets as electrode materials for micro-supercapacitors and sensing materials for glucose sensors [ 103 ]. The designed enzyme-free glucose electrochemical sensor has a high sensitivity of 0.31 μA·μM −1 and a low LOD of 10 μM for sensitive and rapid detection of glucose in blood.…”
Section: Biosensing Applications Of Bimetallic Cpsmentioning
confidence: 99%
“…The 2D NiCo-MOF nanosheet array electrode has excellent glucose detection performance with a linear range of 1 μM~8 mM, fast response time of less than 1 s, sensitivity of 0.6844 mA·mM −1 cm −2 and LOD as low as 0.29 μM ( Figure 4 C). Zha and co-workers used a simple solvothermal method to synthesize 3D nanoflower-like bimetallic NiCo-MOF consisting of 2D nanosheets as electrode materials for micro-supercapacitors and sensing materials for glucose sensors [ 103 ]. The designed enzyme-free glucose electrochemical sensor has a high sensitivity of 0.31 μA·μM −1 and a low LOD of 10 μM for sensitive and rapid detection of glucose in blood.…”
Section: Biosensing Applications Of Bimetallic Cpsmentioning
confidence: 99%
“…The intelligent sensing system with an integrated micro supercapacitor could accurately measure sweat glucose in real time. 181 Another group prepared a non-invasive electrochemical glucose sensor that accurately detects glucose from sweat. The bimetallic-based glucose sensor showed excellent sensitivity and high stretchability and stability.…”
Section: Disease Detectionmentioning
confidence: 99%
“…Zha et al reported on a non-invasive flexible glucose sensor where NiCo-MOFs were exploited as micro-supercapacitor and sensing material. The sensitivity of the prepared bimetallic product was 1422.2 μA mM −1 cm −2 , and upon the integration of the glucose sensor with a micro-supercapacitor on a flexible PET substrate, the authors suggested the potential application for non-invasive sweat glucose detection [ 97 ].…”
Section: Other Body Fluidsmentioning
confidence: 99%